2022
DOI: 10.4414/smw.2022.w30229
|View full text |Cite
|
Sign up to set email alerts
|

Point prevalence of burnout in Switzerland: a systematic review and meta-analysis

Abstract: AIMS OF THE STUDY: To estimate the prevalence of occupational burnout among the Swiss working population.  METHODS: We interrogated three international databases (Medline (PubMed), EMBASE, and PsycINFO) and the databases of 15 Swiss universities to identify studies reporting the prevalence of occupational burnout in Swiss workers over the last 10 years, before the COVID-19 pandemic. Data were summarised descriptively and quantitatively using random-effects meta-analysis. We investigated between-study heterogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 44 publications
1
5
0
Order By: Relevance
“…A study in the USA from 2010 examined the correlation between burnout and medical errors and reported that major medical errors by surgeons are strongly related to a surgeon’s degree of burnout and mental quality of life [ 7 ]. In the current survey, the numbers and burnout rates among hand surgeons (29.1%) are similar to those reported by Pulcrano et al [ 8 ] and higher in comparison to the general Swiss population (18%) [ 9 ]. A lack of control over one’s work life can contribute as a crucial factor to burnout [ 10 ].…”
Section: Discussionsupporting
confidence: 89%
“…A study in the USA from 2010 examined the correlation between burnout and medical errors and reported that major medical errors by surgeons are strongly related to a surgeon’s degree of burnout and mental quality of life [ 7 ]. In the current survey, the numbers and burnout rates among hand surgeons (29.1%) are similar to those reported by Pulcrano et al [ 8 ] and higher in comparison to the general Swiss population (18%) [ 9 ]. A lack of control over one’s work life can contribute as a crucial factor to burnout [ 10 ].…”
Section: Discussionsupporting
confidence: 89%
“…However, work-related stressors, particularly those with moral challenges, can negatively impact mental health 3. Occupational mental health issues like burnout, compassion fatigue and moral distress (MD) have been studied in healthcare workers but less so in other professions facing similar stressors, such as animal care workers 4–6. Animal care workers, including laboratory technicians and veterinarians, are at risk of mental ill health and suicide, particularly due to unique stressors like euthanasia 4 5 7–9.…”
Section: Introductionmentioning
confidence: 99%
“…A recent Delphi consensus statement also highlights burnout as an occupational phenomenon: "In a worker, occupational burnout or occupational physical and Emotional Exhaustion state is an exhaustion due to prolonged exposure to work-related problems" (2). As a professional group, physicians have about twice the risk of burnout as the general workforce (3,4). In a systematic review of 182 studies comprising 109,628 practicing physicians across 45 countries, the prevalence of symptoms of clinical burnout was about 50% (4).…”
Section: Introductionmentioning
confidence: 99%